Occupational safety and health practices in manufacturing industry - Lim, Hui Yee; Abu al-Rejal, Hussein Mohammed (2017)
In today’s world, the economic growth rapidly in industrialization has been given a significant impact of distributions of income and quality of life it is also led in enhance the number of workplace accident in manufacturing industry.In Malaysia, people are still not much aware about the safety and health for the worker on manufacturing industry.Therefore, this study aims to examining the Safety and Health Practices that can be apply in manufacturing industry and identify the benefit of Occupational Safety and Health Practices. Besides that, this study also identified types of hazards, injury and accidents happen in the workplace.This study was carried out in a case of manufacturing sector in Malaysia.The data were collected via an interview with Ong Chuan Hin Rice Mill Sdn Bhd.Qualitative method was employed to achieve all the objectives. Therefore, the data referred in this study consist of the primary and secondary data.Besides, it was found that the selected industry was involved the Safety and Health Practices to reduce the accident happen in workplace.The significant from this study is to improve the knowledge about the Safety and Health Practices to the workers and employees to reduce the accidents in the workplace.